2019
DOI: 10.1002/essoar.10501021.1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Storm-time depletions of multi-MeV radiation belt electrons observed at different pitch angles

Abstract: During geomagnetic storms, the rapid depletion of the high‐energy (several MeV) outer radiation belt electrons is the result of loss to the interplanetary medium through the magnetopause, outward radial diffusion, and loss to the atmosphere due to wave‐particle interactions. We have performed a statistical study of 110 storms using pitch angle resolved electron flux measurements from the Van Allen Probes mission and found that inside of the radiation belt (L* = 3 − 5) the number of storms that result in deplet… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
(74 reference statements)
0
1
0
Order By: Relevance
“…In addition, Olifer et al (2018) conducted an analysis of several storms and suggested that the proximity of the last closed drift shell (LCDS) to the outer boundary of the radiation belts is related to the observed electron loss. Drozdov et al (2019) performed a statistical analysis of the pitch angle distributions during storms that result in a depletion of multi‐MeV electrons and found that in the heart of the outer radiation belt ( L * = 3 − 5), most of the depletions are consistent with EMIC wave activity. Other evidence of the importance of EMIC waves in ultrarelativistic electron loss was found from the analysis of PSD profiles and the formation of PSD minima (Aseev et al, 2017; Shprits et al, 2017, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Olifer et al (2018) conducted an analysis of several storms and suggested that the proximity of the last closed drift shell (LCDS) to the outer boundary of the radiation belts is related to the observed electron loss. Drozdov et al (2019) performed a statistical analysis of the pitch angle distributions during storms that result in a depletion of multi‐MeV electrons and found that in the heart of the outer radiation belt ( L * = 3 − 5), most of the depletions are consistent with EMIC wave activity. Other evidence of the importance of EMIC waves in ultrarelativistic electron loss was found from the analysis of PSD profiles and the formation of PSD minima (Aseev et al, 2017; Shprits et al, 2017, 2018).…”
Section: Resultsmentioning
confidence: 99%